PEMAHAMAN KERANGKA DASAR PENYUSUNAN DAN PENYAJIAN LAPORAN KEUANGAN PSAK PADA AKUNTAN PUBLIK - Murtanto ,; Aufa Kemala (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
The objective of research is to analyze further about understanding framework for the preparation and presentation of financial statements by public accountant.The method used in this research is explanatory method. This study takes 30 public account offices as a sample. The sampling technique in this research is the random method. The instrument that used is descriptive statistics and test of differences by independent sample test. Independent variable is conceptual framework and dependent variable understands of public accountant. In this research, the writer use SPSS 11.5 with a significance level of 5%.The results show that there is a difference understanding level between senior public accountant and junior public accountant.